MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS PADA MAHASISWA ADMINISTRASI RUMAH SAKIT DENGAN MENGGUNAKAN ACTION LEARNING STRATEGY - GINTING, SULASTRI BR; TINAMBUNAN, TEDTY ROHAYA; Apriana, Ana (Jurnal Penelitian Kesmasy, 2024)
There are four skills for studying English: Reading, Listening, Speaking and writing. For administration students Speaking skill is really important to be mastered. The data show that there are many students get struggle for mastering speaking English. They only know how to write and answer the question in writing. Action Learning Strategy helps students to improve the speaking skill by applying the strategy in teaching learning process in the classroom. There are two phases for applying the Action Learning Strategy (ACA) in this research. The data were got from observation, interview, and Speaking skill test. The first phases from observations of the students. The result of observation showed Action Learning Strategy is recommended by students. The data from interviewing shows that there few of students brave to practice or speak in front of classroom. Most of students seldom to speak up in English and prefer wring than speaking. The first phase shows the students’ speaking skill ability score 70. At the second phase, by the observation and interview data showed that students more actively participate on discussion, practice speaking in front of the classroom and had good improvement on English Speaking skill. Applying Action Learning Strategy (ACA) in the teaching learning process on Speaking skill can improve students’ speaking ability for Hospital Administration Students at Institut Kesehatan Deli Husada Deli Tua.